Interventions on Europe's political futures. (September 2017) - McConnell, Fiona; Kuus, Merje; Jeffrey, Alex; Crawley, Heaven; Vaughan-Williams, Nick; Smith, Adrian
Abstract: Europe is facing challenging times. The so-called 'migration crisis' has seen the hardening and militarisation of Europe's borders. Nationalist politicians are framing European states as being under siege from Islamist terrorists and economic migrants, which has led to a rise in xenophobia and casual racism on the streets of European cities. Meanwhile the Euro-zone has seen a series of employment crises and economic bailouts. Alongside such political and economic turmoil, the European Union is facing unprecedented pressures, not least from the 'Brexit' result of the UK's referendum on EU membership in June 2016. In reflecting on these manifold challenges to the idea and space of Europe these interventions focus on three themes that have long animated political geography scholarship: borders, power and crises. Cross-cutting the interventions are two calls to action: to rethink our analytical approaches to Europe, and to reframe our role as critical scholars.